Attitudes and preferences of Malaysian university students towards British English and American English - Wan Shamsuddin, Wan Noor Farah (2018)
Standard British English has often been used as the model to teach and learn English in Malaysia. However, due to the domination of America in the world economy and the eminence of American cultural hegemony portrayed in the mass media, more Malaysians are seemingly attracted to use the American English variety in their daily lives. Much research has been conducted on language attitudes towards the English language, but there seems to be a gap of studies conducted on Malaysian students’ linguistic preferences towards British and American English and the motivations behind their preferences and attitudes towards these two varieties of English. This study attempts to fill this gap by investigating linguistic preferences towards British and American English among 340 Malaysian university students in two linguistic domains: (i) spelling and (ii) lexical choice. This study also explored the composite attitudes of students towards British and American English. Finally, the study examined the motivations behind the students’ preferences and attitudes towards these two varieties. Data were collected via two sets of questionnaires: Questionnaire I involved participants listening to four voice recordings of British and American English speakers to indicate their attitudes and preferences to each spoken variety using the Verbal Guise Technique (VGT) and some attitudinal questions focused on British English and American English whereas Questionnaire II elicited responses towards two linguistic domains: i) Spelling and ii) Lexical preferences. Field notes were also done during the administration of the VGT to observe any change of behaviour among the participants. Following that, a written interview was done with 35 participants to investigate their driving factors and attitudes of the participants towards these two English varieties. Finally, a semi-structured interview was also conducted with ten participants to probe more information based on their answers from the written interview. From this study, the findings were able to suggest some pedagogical implications particularly on the preferred accent in English classroom among Malaysian undergraduate students. The findings do not only suggest the English language use of Malaysian undergraduate students, but also suggest the awareness of the participants on the differences between British English and American English. The study has contributed to the language attitude studies by studying not only the attitudes of Malaysian undergraduate students towards the two main English varieties in Malaysia, but also providing insights into reasons for the attitudes.